2016
DOI: 10.4049/jimmunol.1502355
|View full text |Cite
|
Sign up to set email alerts
|

Mincle Activation and the Syk/Card9 Signaling Axis Are Central to the Development of Autoimmune Disease of the Eye

Abstract: Uveitis, which occurs in association with systemic immunological diseases, presents a considerable medical challenge due to incomplete understanding of its pathogenesis. The signals that initiate T cells to target the eye, which may be of infectious or non-infectious origin, are poorly understood. Experimental autoimmune uveoretinitis (EAU) develops in mice immunized with the endogenous retinal protein interphotoceptor retinoid binding protein (IRBP) in the presence of the adjuvant CFA. EAU manifests as poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 48 publications
(56 reference statements)
2
71
0
Order By: Relevance
“…5). This effect was only partially lost in LPS‐primed BMDC from TLR4 knockout mice, indicating that the M. tuberculosis ligands in this extract were acting by additional pathways, such as TLR2 and Dectin‐1 48. These data for the first time show that LPS (endotoxin) “heterotolerance” or “crosstolerance” to M. tuberculosis ligands, i.e.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…5). This effect was only partially lost in LPS‐primed BMDC from TLR4 knockout mice, indicating that the M. tuberculosis ligands in this extract were acting by additional pathways, such as TLR2 and Dectin‐1 48. These data for the first time show that LPS (endotoxin) “heterotolerance” or “crosstolerance” to M. tuberculosis ligands, i.e.…”
Section: Resultsmentioning
confidence: 81%
“…Mycobacterium tuberculosis activates DC through several ligands including TLR2 and Dectin‐1, and less so TLR4 with downstream activation of the inflammasome and secretion of IL‐1 β . Furthermore, Dectin‐1, Mincle and signalling through the Syk/Card 9 complex are required for induction of EAU by way of IRBP:CFA 48, 49. As signalling by the IL‐1 receptor has recently been shown to be critical for the induction of EAU,50 it is a distinct possibility that LPS‐primed BMDC prevent IRBP:CFA‐induced EAU by blocking BMDC inflammasome activation and IL‐1 β production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published results indicate that signaling through Mincle plays a role in obesity-induced adipose tissue inflammation and the subsequent adipose tissue fibrosis (28). Recently, an essential role of Mincle signaling through the Syk/Card9 axis in the development of autoimmune eye inflammation in a model of experimental autoimmune uveoretinitis was revealed (29). It was shown that Mincle signaling promotes pancreatic oncogenesis, whereas the deletion of Mincle protects against oncogenesis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have focused on defining the precise molecular mechanism of CARD9 signalling and exploring its role in the development of non‐infectious disease including cardiovascular diseases 9, 10. Obesity and type 2 diabetes (T2D) have become the leading health problem in the world.…”
Section: Introductionmentioning
confidence: 99%